Jury Sentencing in Noncapital Cases: A Case Study of El Paso County, Texas - Weninger, Robert A. (1994)
Critics of jury sentencing in noncapital cases complain that jurors are less competent or qualified than judges to decide questions about probation or incarceration. Thus far, however, views on jury sentencing in noncapital cases have rested largely on speculation, not on empirical evidence